Environmental constraints' sensitivity of soil organic carbon decomposition to temperature, management practices and climate change. (December 2019) - Dash, P.K.; Bhattacharyya, Pratap; Roy, K.S.; Neogi, S.; Nayak, A.K.
Highlights: Environmental constraints (ECs) are the processes that slow down soil organic carbon (SOC) decomposition rates. ECs determine the apparent temperature sensitivities of SOC pools. Physical, chemical and biochemical ECs impart relative stability to SOC. ECs are sensitive to temperature, management practices and climate changes. ECs are sensitive to tillage, land use changes, water management and microbial manipulation. Abstract: Intrinsic temperature sensitivity of soil organic carbon (SOC) pools is the inherent response of their decomposition rate to temperature. It primarily depends on the chemical structure of SOC pool and ambient temperature. The apparent temperature sensitivity of SOC pools refers to the observable temperature sensitivity which primarily depends on environmental constraints (ECs) The Environmental constraints are key indicators that determine the apparent temperature sensitivities of different SOC pools. The ECs are the processes and or factors that slow down organic carbon (OC) decomposition rates and dampen intrinsic temperature sensitivities. These are broadly classified as physical, chemical, biological and biochemical processes those impart relative stability to SOC. The major ECs include; soil aggregation, flooding, clay associated-C and microbial secreted exo-polysachharide, etc. However, the matter of concern is that the ECs are also sensitive to temperature, management practices and climate change. Uncertainties exist with the stability and sensitivity of ECs to various management systems and climate induced anticipated changes. We reviewed in details the various types of ECs and how they are sensitive to management practices like tillage, land use changes, nutrient and water management, priming effect due to carbon dioxide (CO2 ) fertilization, vegetation composition and microbial manipulation.